The Economics of Internal Migration: Advances and Policy Questions - Ning Jia; Raven Molloy; Christopher L. Smith; Abigail Wozniak (Institute of Labor Economics (IZA), 2022)
We review developments in research on within-country migration, focusing on internal migration in the U.S. We begin by describing approaches to modelling individuals' migration decisions and equilibrium outcomes across local areas. Next, we summarize evidence regarding the impact of migration on individuals' outcomes, implications of migration for local labor market adjustment, and interactions between migration and housing markets. Finally, we discuss evidence on the efficacy of policies aimed at encouraging migration and conclude by highlighting important unanswered questions that are critical for informing migration-related policy.
Keywords: J61; J68; J11; 330; migration; internal migration; labor market adjustment; housing markets; migration policy; migration theory